Pengaruh Motivasi, Disiplin Kerja dan Gaya Kepemimpinan Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Intervening Pada PT. Kilang Lima Gunung - Alif Juliandra Khaira; Vicky Brama Kumbara; Nia Nadilla (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of work motivation, work discipline, and leadership style on employee performance with job satisfaction as an intervening variable at PT Kilang Lima Gunung Padang. The background of this study is the importance of improving employee performance through effective management of work motivation, work discipline, leadership style, and job satisfaction. This research employed a quantitative approach using a survey method. The population and sample consisted of all 57 employees of PT Kilang Lima Gunung Padang, selected using the total sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the assistance of SmartPLS 3.0 software. The results indicate that work motivation has a positive and significant effect on job satisfaction. Work discipline also has a positive and significant effect on job satisfaction, whereas leadership style has a positive but insignificant effect on job satisfaction. Furthermore, work motivation, work discipline, and leadership style each have a positive and significant effect on employee performance. Job satisfaction also has a positive and significant effect on employee performance. The indirect effect analysis reveals that job satisfaction mediates the relationship between work motivation and employee performance. However, job satisfaction does not mediate the relationship between work discipline and employee performance or the relationship between leadership style and employee performance. The findings of this study are expected to serve as a reference for the management of PT Kilang Lima Gunung Padang in formulating human resource management policies to enhance employee job satisfaction and performance